Kesan Harmonik Sistem Kuasa Ke Atas Transformer Pengagihan Dan Rekabentuk Baru Dengan Mengambil Kira Transformer Factor-K - Jaafar, Mohd Khairul Munir (Universiti Sains Malaysia, 2006)
Increases of non linear load on power system will reduce the transformer’s life expectancy. Distribution transformer manufacturers have been used the rating system called K-factor to ensure that the transformer can operate safely when suppying non-sinusoidal load current. This report was provided to show the effect of harmonic on the distribution transformer from the experiment done to single phase transformer 250VA. The effect of harmonic was investigated where linear and non linear load was connected to transformer. The load used in the experiment is pure resistance and rectifier. The experiments were done to investigate the effect of harmonic to the transformer such as losses, efficiency and temperature rise. Besides this report was included with the method used to reduce the harmonic effect to the transformer that is by using the derating method. Two derating method used is as recommended by standard of IEEE C57.110-1986 and BS 7821. The results show that there were increases in transformer losses, reduction of transformer efficiency and higher temperature rise compare to the linear load.